Temporal and spatial trends in gastric cancer burden in the USA from 1990 to 2021: findings from the global burden of disease study 2021 - Zhan, Chengwei; Qiu, Binxu; Wang, Jun; Li, Yanhua; Yu, Jinhai (Frontiers in Oncology, 2024)
BackgroundGastric cancer (GC) is a significant public health concern in the USA, and its burden is on the rise.MethodsThis study utilized the latest data from the Global Burden of Disease (GBD) study. We provided descriptive statistics on the incidence, prevalence, mortality, disability-adjusted life years (DALYs), and age-standardized rates (ASRs) of GC across the USA and states. By calculating percentage changes and average annual percentage changes (AAPC), along with conducting age-period-cohort analysis, we assessed the trends in the burden of GC. Decomposition analysis was then performed, followed by the application of an autoregressive integrated moving average (ARIMA) model to forecast changes in ASRs through 2036.ResultsFrom 1990 to 2021, the number of incidence and prevalence of GC in the USA increased, but age-standardized incidence rates (ASIR) trended downward (AAPC = -0.73, 95% confidence interval [CI]: -0.77 to -0.68) and age-standardized prevalence rates (ASPR) (AAPC = -0.99, 95% CI: -1.08 to -0.9) showed a decreasing trend. In addition, the number of deaths, DALYs, age-standardized mortality rates (ASMR) and age-standardized DALYs rates (ASDR) in GC showed a decreasing trend. The burden of GC was significantly higher in males compared to females. In addition, we found that the highest incidence and prevalence in females was in the age group of 75-79 years, whereas the highest incidence and prevalence in males was in the age group of 70-74 years.ConclusionGC is a major public health issue in the USA. Although ASIR, ASPR, ASMR, and ASDR for GC are decreasing, the number of incidence and prevalence of GC in the USA remains high, and the disease burden of GC in the USA remains high. Strengthening preventive interventions, particularly for men and patients over the age of 60, will be crucial in the future.